The effects of resistance training on road cycling performance among highly trained cyclists: A systematic review - Yamamoto, L. M.; Klau, J. F.; Casa, D. J; Kraemer, W. J.; Armstrong, L. E.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2010)
Highly trained cyclists may be hesitant to incorporate resistance training (RT) with their endurance training (ET) because of the mixed data regarding concurrent RT and ET (CT). The purpose of this review was to search the scientific body of literature for randomized controlled trials (RCTs) of CT on road cycling performance for highly trained cyclists. Key words (including cycling and strength training) were used to search relevant databases through September 2009 for literature related to CT. Randomized controlled trials were included if they scored =5 on the Physiotherapy Evidence Database scale. Five studies met the inclusion criteria: highly trained road cyclists (>7 h·wk-1 or > 150 km·wk-1, with at least 6 months of training), outcome measure was cycling performance (time trial or time to exhaustion), and RT performed off-bike. Two of the 5 studies found no improvement in performance with CT, but these studies added RT on top of the athletes' existing ET. The 3 studies with improved cycling performance replaced a portion of the athletes' ET with RT, and 2 of the 3 studies included high-intensity explosive-type resistance exercises. Despite the limited research on CT for highly trained cyclists, it is likely that replacing a portion of a cyclist's ET with RT will result in improved time trial performance and maximal power.